Aging and Brain Atrophy in Multiple Sclerosis. Issue 4 (10th May 2019) - Ghione, Emanuele; Bergsland, Niels; Dwyer, Michael G.; Hagemeier, Jesper; Jakimovski, Dejan; Paunkoski, Ivo; Ramasamy, Deepa P.; Carl, Ellen; Hojnacki, David; Kolb, Channa; Weinstock‐Guttman, Bianca; Zivadinov, Robert
ABSTRACT: BACKGROUND AND PURPOSE: Brain atrophy accelerates at the age of 60 in healthy individuals (HI) and at disease onset in multiple sclerosis (MS) patients. Whether there is an exacerbating effect of aging superimposed on MS‐related brain atrophy is unknown. We estimated the aging effect on lateral ventricular volume (LVV) and whole brain volume (WBV) changes in MS patients. METHODS: 1, 982 MS patients (mean follow‐up: 4.8 years) and 351 HI (mean follow‐up: of 3.1 years), aged from 20 to 79 years old (yo), were collected retrospectively. Percent LVV change (PLVVC) and percent brain volume change (PBVC) on 1.5T and 3T MRI scanners (median of 3.9 scans per subject) were calculated. These were determined between all‐time points and subjects were divided in six‐decade age groups. MRI differences between age groups were calculated using analysis of covariance (ANCOVA). RESULTS: Compared to HI, at first MRI, MS patients had significantly increased LVV in the age groups: 30–39 yo, 40–49 yo, 50–59 yo, 60–69 yo (all P < .0001), and 70–79 yo ( P = .029), and decreased WBV in the age groups: 20–29 yo ( P = .024), 30–39 yo ( P = .031), 40–49 yo, and 50–59 yo (all P < .0001). Annualized PLVVC was significantly different between the age groups 20–59 and 60–79 yo in MS patients ( P = .005) and HI ( P < .0001), as was for PBVC in MS patients ( P = .001), but not for HI ( P = .521). There was a significant aging interaction effect in the annualized PLVVC ( P = .001) between HI and MS patients, which was not observed for the annualized PBVC ( P = .380). CONCLUSIONS: Development of brain atrophy manifests progressively in MS patients, and occurs with a different pattern, as compared to aging HI. PLVVC increased across age in HI as compared to MS, while PBVC decreased across ages in both HI and MS.